Tratamiento de hepatopatías equinas con silimarina (Veterinary Science, 2017)
Authors treated nine horses that showed hepatic disease with 0.3g/100 kg of silymarin, active principle of Silybium marianuum. before animals were treated they were evaluated, through clinical sintoms, serum analysis: hepatic enzymogram, cholesterol, uremia, proteins, total and direct billirrubin and bromusolfaftalein functional test. All equines showed clinical remission confirmed after treatment through serum levels and functional test
Keywords: Equine; Silimarin; Liver